Kode Vicious: Beautiful Code Exists, If You Know Where to Look. - Neville-Neil, George V. (Communications of the ACM, 2008)
The article discusses computer code, examining hardware performance monitoring counters (hwpmc) on the FreeBSD operating system. HWPMC is implemented in hardware, the author indicates, in this case the hardware of the central processing unit (CPU). Topics include the confusing nature of the code, compilers that generate suboptimal code, and computer programmers who write good code. Also discussed is reading header files before the code, lines that indicate well-written code, and the inclusion of patch version numbers.